Evaluation of the antioxidant capacity of potato (Solanum tuberosum) - Wale, Janet Lorenzo; Rowena Grace O. Rumbaoa (2008.)
ABSTRACT Four varieties of potato (Solanum tuberosum), namely: Igorota, Purple potato, Bengueta and Ganza, which are commercially grown in the Philippines, were evaluated for their total phenolic content, total antioxidant activity, DPPH radical scavenging effect, reducing power and iron chelating capacity. Total phenolic content ranged from 43.83 to 66.97 mg GAE/100g. Antioxidant activity was found to increase with the concentration of the methanolic extract of potato. Among the potato varieties, Bengueta at 50 mg/ml had the highest (44.21%) total antioxidant activity, followed by Purple potato (31.24%), Ganza (21.69%) and Igorota (18.82%). Radical scavenging activity in terms of EC50 expressed as μg GAE showed the order of Bengueta> Ganza > Igorota > Purple potato. On the other hand, Ganza had the highest reducing power (EC50 = 71.56) among the potato varieties, whereas Igorota had the highest chelating capacity (EC50 = 13.81). A weak correlation between total antioxidant activity and total phenolic content was determined in potato (r = 0.029), whereas DPPH radical scavenging effect (r = -0.569) was significantly (p<0.05) correlated to total antioxidant activity. These results suggest varying mechanisms for the antioxidant property of potato and that substances other than phenolics contribute to the antioxidant activity. Results also suggest that potato can be a potential source of antioxidants that may protect cells from oxidative damage.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Potatoes -- Philippines; Potatoes -- Philippines -- Analysis